2012
DOI: 10.1186/1550-2783-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein to maximize resistance training: a review and examination of protein spread and change theories

Abstract: An appreciable volume of human clinical data supports increased dietary protein for greater gains from resistance training, but not all findings are in agreement. We recently proposed "protein spread theory" and "protein change theory" in an effort to explain discrepancies in the response to increased dietary protein in weight management interventions. The present review aimed to extend "protein spread theory" and "protein change theory" to studies examining the effects of protein on resistance training induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
(106 reference statements)
1
29
0
2
Order By: Relevance
“…These observations complement our previous research showing that changes in protein intake predict changes in bone mineral density (inverse association) in older women (59) and support that muscle and strength gains from resistance training are augmented by greater increases in habitual TPro from before to during the intervention (60). Collectively, these findings indicate that CTPro should be carefully documented and assessed as a potential BC modifier.…”
Section: Discussionsupporting
confidence: 85%
“…These observations complement our previous research showing that changes in protein intake predict changes in bone mineral density (inverse association) in older women (59) and support that muscle and strength gains from resistance training are augmented by greater increases in habitual TPro from before to during the intervention (60). Collectively, these findings indicate that CTPro should be carefully documented and assessed as a potential BC modifier.…”
Section: Discussionsupporting
confidence: 85%
“…Optimization of resistance training and the pattern of adaptive changes related to the development of muscular strength and power have been the focus of interest of scientists from different fields of studies [3][4][5][6]. In addition to training, diet and supplementation also have a significant effect on adaptation and post-exercise responses [7][8][9][10][11][12]. To date, few supplements have been shown to have a direct ergogenic effect on physical capacity.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is not unfounded given that a 14 g bolus of supplemental protein has been shown to reduce food intake during a subsequent meal [27] . Notwithstanding, our finding that total protein intake did not increase in both groups is problematic given that others have suggested that protein supplementation has to be 'deliberate' in order to realize optimal training adaptations; specifically intakes should exceed 66% of pre-supplementation values [28] or be greater than 2.0 g/kg/day in men [29] and subjects in both groups consumed ∼ 1.1-1.3 g/kg during T2 and T3. Given that protein metabolism has been reported to be minimally affected by gender [30] , we surmise that women in the current study may have experienced greater increases in muscle mass if daily protein intakes were ∼ 2.0 g/kg/day during the study.…”
Section: Discussionmentioning
confidence: 66%